Watkins Family Visiting Christine's Cousin Richard Graham and His 2 Sons - Watkins, Howard::::::::: (1989)
Adam, Peter Graham, Robin, Richard Graham, Howard and Jesse Graham at restaurant; UC Memorial Stadium painting